Efficacy and safety of cannabidiol for the treatment of pediatric epilepsy - ABDULAZIZ ALRABAT1, BADER MOHAMMAD ALMALKI2, Alghamdi, Raid Hassan D3, Naif Abdulrahman alotibi4, omar owaydhah salem almotairi1, Wedad musleh sarazid1, Rayid Hassan Ahmed Alzahrani5 (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Drug-resistant epilepsy affects one-third of patients, requiring new medications for efficacy. Interest in new antiepileptic properties, targeting novel receptors, is high.Objectives: Determine which studies have examined the usage of cannabis & products derived from cannabis as a therapy of pediatric epilepsy.Patients and methods: NRSs and RCTs examining the usage of cannabis as a therapy for any form of epilepsy in kids (eighteen years old or less) have been involved into our analysis. The interventions involved a wide range of cannabis-derived products, such as THC, cannabinol, CBD, or combinations, delivered through various routes (such as inhalation, oral). Pharmacologic (such as analgesics) & nonpharmacologic (such as vagus nerve stimulation, resective brain surgery ,diet therapy) therapies, in addition to placebo, standard care, or no treatment, were eligible comparators.Results, Conclusion: The administration of CBD resulted in a significant improvement of seizure load. Most kids reported a reduction in the incidence of their seizures. kids with drug-resistant Dravet & Lennox-Gastaut syndromes can benefit from CBD in terms of reduced seizure burden (moderate certainty); nonetheless, few of these children were completely seizure free. Children with other DRE syndromes may also benefit, albeit the evidence is currently limited. It is not appropriate to apply these results to all cannabis-based products, particularly ones whose exact makeup is unknown.